PENGARUH KUALITAS PELAYANANTERHADAP VOLUME PENJUALAN PADA CV. MADALA KECAMATAN FANAYAMA - Ndruru, Dewi Selviian (Jurnal Ilmiah Mahasiswa Nias Selatan, 2024)
Study scope of this is a examine in quality service the in terms of sales volume in CV. Madara, regent of Southern Nia. of this to clarify The purpose the study was relationship between service quality and sales volume in CV. Madara, Fanayama District, Southern Near Regency. quantitative using The method used is multiple linear regression analysis techniques at uses data from a questionnaire he distributed to 37 consumers listed in his resume. Madara Fanayama, Regent of Southern Nia. discussion presented and Based on the data, we can conclude service influences of that the quality the volume of sales in CV. Madara, Fanayama District, Southern Near Regency. This can be explained as follows. The results show (X) the service quality variable significant effect on the sales has a positive variable volume (Y), with tcount (3,762) > ttable (1,691) and a significance level of < 0.001. I was0.05. means thid that variable promotion (X) has a positive and significant impact on resume sales volume (Y). Madara, Fanayama District, Southern Near Regency. of the study show The results a of determination coefficient (R^2) of 0.742, but we find that 74.7% of the variability in the dependent variable (sales) can be explained by the independent variables (advertising and services). The remaining 25, 3% are influenced by other variables outside the model..